2021
DOI: 10.3390/genes12030444
|View full text |Cite
|
Sign up to set email alerts
|

Genome Analysis of Endotrypanum and Porcisia spp., Closest Phylogenetic Relatives of Leishmania, Highlights the Role of Amastins in Shaping Pathogenicity

Abstract: While numerous genomes of Leishmania spp. have been sequenced and analyzed, an understanding of the evolutionary history of these organisms remains limited due to the unavailability of the sequence data for their closest known relatives, Endotrypanum and Porcisia spp., infecting sloths and porcupines. We have sequenced and analyzed genomes of three members of this clade in order to fill this gap. Their comparative analyses revealed only minute differences from Leishmaniamajor genome in terms of metabolic capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 117 publications
0
11
0
1
Order By: Relevance
“…Prior to the release of our genome, there were no genome sequences for genus Porcisia . Subsequently, the partial genome of P. deanei was released and published 15 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Prior to the release of our genome, there were no genome sequences for genus Porcisia . Subsequently, the partial genome of P. deanei was released and published 15 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Endotrypanum monterogeii and Porcisia spp., being dixenous parasites of sloths and porcupines, respectively, represent the closest known relatives of Leishmania. The recently published analysis of their genomic sequences shed light on the evolution of pathogenicity in dixenous Leishmaniinae, which appears to be shaped mainly by changes in the amastin repertoire [ 78 ].…”
Section: Dixenous Leishmaniinaementioning
confidence: 99%
“…Some examples are provided below. The analysis of amastins, a large family of surface glycoproteins expressed primarily in amastigotes, revealed that δ-amastin subfamily is restricted to the dixenous Leishmaniinae and its expansion has likely happened in the ancestor of the genus Leishmania [ 78 , 125 ]. The repertoire of adenylate cyclases has expanded in dixenous trypanosomatids and many genes encoding these proteins pseudogenized in those subspecies of T. brucei , which lost the ability to develop in insects [ 126 ].…”
Section: Other Applications Of the Trypanosomatid Genomic Datamentioning
confidence: 99%
“…Initially classified as Leishmania hertigi , subsequent phylogenetic studies resulted in its reclassification into a new genus, Porcisia ( 3 ), within the subfamily Leishmaniinae ( 4 ). To date, only a partial assembly of Porcisia deanei ( 5 ) (strain TCC258) is available within this genus. We now assemble the complete genome sequence of Porcisia hertigi , strain LV43, isolate C119 (WHO code MCOE/PA/1965/C119;LV43), isolated from a porcupine in Panama in 1965.…”
Section: Announcementmentioning
confidence: 99%